A framework to facilitate te leadership performance improvement in the healthcare sector: the case of the kingdom of Saudi Arabia - Algarni, Namshan (Cranfield University, 2018)
In order to improve leadership performance and enhance effective leadership in the healthcare sector organisations in general and the Kingdom of Saudi Arabia (KSA) in particular, this study proposes a theoretical framework to address the ways in which leadership competency strengthens the relationship between leaders and followers. The research is based on a single case as a longitudinal study to allow for in-depth investigation. The research applies a constructive-interpretivism approach – inductive to gain a deep understanding and clear explanation of the leadership performance and practices in the organisational setting. The data were collected using triangulated methods—semi-structured interviews, focus groups and observation. This research applies a qualitative strategy to achieve its objectives. This approach, is most appropriate for this research, which is exploratory and interpretive in nature. This study targets participants who are experts in the phenomena of the field study. The participants represented several levels of the organisations studied. Data were collected in three stages, using issue focus in-depth interviews. The saturation level was reached after 33 interviews. A number of elements emerged as important in shaping the leadership performance in the field study, in the areas of culture, values and context. The present study suggested a framework to facilitate a culture of leadership performance improvement in the healthcare organisations. This framework was developed based on the main emerged themes of the study. This study is expected to contribute to the existing literature on leadership competencies, the process of change management and social identity by providing empirical data on the significance of leadership competency in improving performance in the healthcare sector in general, especially in the KSA and the Gulf Cooperation Council (GCC countries).
Keywords: Saudi Arabia; leadership; competencies; healthcare sector; culture; change management